The Seduction of a Drug Mule: Drug Trafficking Among Female Offenders - Sumter, Melvina T. (Journal of drug issues, 2024)
This research examined how women are recruited into drug trafficking. Previous findings indicate that women are recruited into drug trafficking due to economic hardship. Data for this research study is taken from in-depth interviews with 13 female offenders incarcerated at the Trinidad and Tobago Prison Service. The findings in this study suggest women become involved in drug smuggling for reasons that are far more complex than simple financial need. Specifically, the majority of women fell prey, under the guise of friendship, to an unscrupulous individual, interested in furthering his or her cause. Under systems of patriarchy and capitalism, the findings from this study suggests that women became involved in drug trafficking because of how they are socialized.